Kemampuan Berpikir Kreatif Matematis Ditinjau dari Resiliensi Matematis Siswa dalam Pembelajaran Problem Based Learning Berbantuan Seesaw - Iqbal, Mohammad; Junaedi, Iwan; Wardono, Wardono (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The aim of the research is to evaluate, identify, categorize the level of mathematical creative thinking ability and determine the influence of mathematical resilience on mathematical creative thinking ability in class VIII at SMP Negeri 10 Semarang city before and before implementing the modelProblem Based Learning helpSeesaw. The type of research in this research is quantitative. The research method used is a quantitative method with a One Group Pretest-Posttest design. The data collection technique uses creative thinking ability tests for pretest and posttest with number content. Meanwhile, the data analysis technique used is the average difference (Independent Sample T-Test), Gain test, and Simple Regression Test. The research results show that based on the results of the average difference test, there are differences in scores before and after applying the modelProblem Based Learning (PBL) assisted by Seesaw can improve mathematical creative thinking skills with an average score for each before and after the model is applied, namely 46 and 76 with categorization of improvement based on the Gain test after the Problem Based Learning (PBL) model assisted by Seesaw is applied, namely 5 students with low improvement, 18 students with moderate improvement, and 9 students with high improvement and the average increase of students after applying the Problem Based Learning model assisted by Seesaw was included in the medium category, and there was an influence of mathematical resilience on students' mathematical creative thinking abilities. The conclusions in this research are Applying the PBL model assisted by Seesaw can improve creative mathematical thinking skills in class VIII students at SMP Negeri 10 Semarang